Satputia Kashi Khushi to make farmers cheer - Choudhary, B R; Pandey, Sudhakar; Choudhary, B R (Indian Horticulture, 2019)
Kashi Khushi originated from an open-pollinated land race collected from Kushinagar, Uttar Pradesh, in 2006, was developed by continuous inbreeding up to 10 generations and single plant selection from the original population (VRS-1). The single plant selection was based on earliness, internodal length, fruit size, number of fruits/cluster, yield and tolerance to mosaic and downy mildew. It provides 120-140 q fruits from one hectare land.